Characteristics of entrepreneurs and successful food service ventures in Zamboanga City - Domen, Antonietta Hachero; Catral, Ma. Lourdes D. (2005)
This is a descriptive survey and case study of the characteristics of entrepreneurs and successful food services ventures in Zamboanga City, conducted with the following objectives: to study the entrepreneurs in terms of demographic, professional, socio-cultural background, and personal entrepreneurial characteristics; to describe the business characteristics and success indicators. The study tried to determine correlations between characteristics of entrepreneurs with the success indicators of their businesses. A qualitative discussion of entrepreneurs in Zamboanga City was presented trough a case study. The sources of data for the study were the entrepreneurs of food service establishments selected through purposive sampling. Statistical measures were in the form of percentages, means and correlation tests. The study showed that the mean age of entrepreneurs was 47. Most of them were females and married. Majority were college graduates, a third had managerial positions, and half of them had attended more than one training program. Most of the food service establishments were operated as sole proprietorship. Half of the restaurants were full service with an average seating capacity of 50-100 customers per day. In terms of socio-cultural background, the respondents were more democratic than autocratic in upbringing and had early exposure to business. Data for values and beliefs were categorized into four, namely: fate, belief in self, connections, and value for money. Data showed that the entrepreneurs were moderately strong in these traits. Connections had the highest mean and belief in self had the lowest. Most of the grew up with parents. Data showed that more than half of their parents were in business when they were young. The study on Personal Entrepreneurial Characteristics (PECs) yielded 10 strong to moderate characteristics. Based on this scale, the Zamboanga food service entrepreneurs could be described as particularly strong in: commitment to work, goal setting, information seeking, systematic planning and monitoring, self-confidence, and highly demanding in quality and efficiency at work. They could also be said to be moderately possessing risk taking abilities, persuasion and networking. Business success indicators used were data on assets, sales volume, net income, and increase in manpower and age of the business. The first and the last indicator did not yield any significant correlations with any of the variables. Sales volume as a business success indicator had significant negative correlations with the following: a correlate on professional background; 'previous positions held'; personality traits on 'goal setting' and 'systematic planning and monitoring'. Connections, a variable on values and beliefs, though not significantly correlated had values that implied a slight positive relationship. Net income as another business success indicator had a negative significant correlation with democratic upbringing, exposure to business while young and information seeking. A positive correlate was personality trait on 'pursuit for quality and efficiency'. Another business success indicator, increase in the number of manpower of the business was significantly but negatively correlated to gender, while positively correlated to 'connections'. Likewise, number of manpower could be said to be closely associated with their belief on having good connections with those who were known to be powerful, and who have high positions in the locale. The Zamboanga entrepreneurs' value for references from friends regarding manpower hiring may have influenced the increase in manpower. The variables on Personal Entrepreneurial Characteristics which had positive significant correlations with a success indicator was demand for quality and efficiency and connections while all the other significant variables had negative values. Demand for quality and efficiency, characteristic of the entrepreneurs which had high ratings derived from their positive responses was closely associated with income. The value of this trait is recognized in managing a business and maintaining its profitability. Their hardworking traits, an attempt to put quality in their businesses, positively influenced their income. On the whole, those with negative correlations for the purposes of discussion might be explained as a function of time and congruence. Although the establishments had experienced some degree of success at one time or another, the economic slump at the time of the survey may have masked the relationship of the traits with the success indicators. The characteristics which were postulated to be commonly possessed by entrepreneurs, as written in literature and research cases were found to be present and strong among the respondent entrepreneurs in Zamboanga. While results showed that a number of traits were not significantly correlated to success, this study needs to be validated in a higher level study. The case study on two establishments were supportive of the assumptions on success factors. The data validated the strong presence of personality entrepreneurial traits, particularly on persistence and commitment to work. Both entrepreneurs come from hardworking parents, who taught the values of hard work and self reliance and handed over the reigns of the business to them at a young age. Their backgrounds showed persistence and motivation despite recurring crisis typical of the place. Based on the results of the study, recommendations are still in the direction of developing entrepreneurs at an early age, but exposure to business should be honed with education and formal training in management. Development should not only be in the form of formal training but also in shaping the orientation of the person towards the entrepreneurial traits studied, particularly on persistence, commitment to work contract, goal setting, persuasion and networking, and the rest. The instrument PECs can be used as a self rating measure for training on entrepreneurship. It is also recommended that a similar study be conducted with definitive parameters for indicators of success. The methodology should ensure accurate data on sales and timeliness of data collection. Based on the interesting results of the case study, further research can be continued along this line.
Thesis (M. Food Service Administration)--University of the Philippines, Diliman.
Keywords: Businesspeople -- Training of -- Philippines -- Zamboanga City; Businesspeople -- Education -- Philippines -- Zamboanga City; Businesspeople -- Philippines -- Zamboanga City -- Attitudes; Businesspeople. -- Philippines -- Zamboanga City -- Social conditions; Businesspeople -- Philippines -- Zamboanga City -- Psychology; Entrepreneurship -- Philippines -- Zamboanga City; Food service management -- Philippines -- Zamboanga City